2021
DOI: 10.3906/sag-2006-146
|View full text |Cite
|
Sign up to set email alerts
|

Long term neurological sequela of isolated infarctions according to the topographic areas of thalamus

Abstract: Background/aim: Thalamus infarctions presented with various clinical findings are considered to be related to classical and variative infarction areas. In our study, we aimed to compare the sequela clinical findings of patients with isolated thalamus infarction according to anatomical areas.Methods: 70 patients diagnosed with isolated thalamus infarction in our clinic between 2010 and 2020 were included in the study. The infarction areas of the patients were divided into groups by the radiologist, including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Further exploration is required to identify component responsible for the beneficial effect of coffee, such as caffeine and phenolic acids, to develop medication for improving cognitive abilities after stroke. Ample literature has consistently showed acute and long-term cognitive disorders ( 31 34 ) despite initial improvements ( 35 ) in patients with thalamic stroke, which is possibly attributed to impairments of frontal lobe-related functions. In this study, we found thalamus infarctions were associated with cognitive recovery in the early phase after stroke among patients with post-stroke SCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further exploration is required to identify component responsible for the beneficial effect of coffee, such as caffeine and phenolic acids, to develop medication for improving cognitive abilities after stroke. Ample literature has consistently showed acute and long-term cognitive disorders ( 31 34 ) despite initial improvements ( 35 ) in patients with thalamic stroke, which is possibly attributed to impairments of frontal lobe-related functions. In this study, we found thalamus infarctions were associated with cognitive recovery in the early phase after stroke among patients with post-stroke SCC.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found thalamus infarctions were associated with cognitive recovery in the early phase after stroke among patients with post-stroke SCC. These patients with thalamic stroke presented with early cognitive improvements, perhaps because infarction areas of almost all patients were not in the anterior area ( 33 , 34 ), and seven patients had right-sided lesions in 10 subjects with objective cognitive recovery ( 32 , 35 ). However, there was no appropriate explanation for this observation due to lack of long-term investigation and the detail of neuroimaging data.…”
Section: Discussionmentioning
confidence: 99%